CRP Livestock Vietnam Priority Country - RHoMIS COVID19 Survey - Hammond, James; Mai Tu; Teufel, Nils; Wijk, Mark T. van; Douxchamps, Sabine (International Livestock Research Institute, 2023)
A survey of the impacts and recovery from those impacts due to COVID19 and the related control measures conducted in the research sites of the CRP Livestock Vietnam Priority Country.